2015
DOI: 10.1111/jicd.12162
|View full text |Cite
|
Sign up to set email alerts
|

The effect of working time on the displacement of Biodentine beneath prefabricated stainless steel crown: a laboratory study

Abstract: Within the limitations of this in vitro study, a GIC-loaded SSC can be seated on Biodentine placed into a pulp chamber 3 min after mixing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 19 publications
1
5
0
Order By: Relevance
“…This finding is also in line with previous findings (20) that attributed the shortened setting time of Biodentine ® to the presence of calcium chloride in the original liquid (21). On the other hand, Dawood et al (22) suggested that glass-ionomer cement loaded stainless steel crowns could be seated on Biodentine ® placed into a pulp chamber 3 min after mixing. However, despite the shorter setting time of Biodentine ® than that of MTA, the initial setting of Biodentine ® is approximately 12-15 min, which is still a long period of time, especially for paediatric patients (22).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This finding is also in line with previous findings (20) that attributed the shortened setting time of Biodentine ® to the presence of calcium chloride in the original liquid (21). On the other hand, Dawood et al (22) suggested that glass-ionomer cement loaded stainless steel crowns could be seated on Biodentine ® placed into a pulp chamber 3 min after mixing. However, despite the shorter setting time of Biodentine ® than that of MTA, the initial setting of Biodentine ® is approximately 12-15 min, which is still a long period of time, especially for paediatric patients (22).…”
Section: Discussionsupporting
confidence: 92%
“…When mixed with their original liquids, the setting time of MTA was significantly longer than that of Biodentine. On the other hand, Dawood et al (22) suggested that glass-ionomer cement loaded stainless steel crowns could be seated on Biodentine ® placed into a pulp chamber 3 min after mixing. On the other hand, Dawood et al (22) suggested that glass-ionomer cement loaded stainless steel crowns could be seated on Biodentine ® placed into a pulp chamber 3 min after mixing.…”
Section: Discussionmentioning
confidence: 99%
“…The short setting time of Biodentine is a clinical advantage over the other long setting‐time CSC, especially in situations that warrant definitive treatment in a single visit, such as in pediatric dentistry. Furthermore, an in vitro GIC‐loaded stainless steel crown can be placed over Biodentine 3 min after mixing, without displacing the Biodentine significantly …”
Section: Clinical Applications Of Biodentinementioning
confidence: 99%
“…Furthermore, an in vitro GIC-loaded stainless steel crown can be placed over Biodentine 3 min after mixing, without displacing the Biodentine significantly. 88 Because of its favorable physical properties, good handling characteristics, short setting time, bioactivity, biomineralization potential, sealing ability, and lower cost than MTA, Biodentine could be an appropriate alternative to MTA.…”
Section: Clinical Applications Of Biodentinementioning
confidence: 99%
“…Dawood et al, [43] reported that Biodentine can be used in pediatric dentistry as its short setting time especially in situations that warrant definitive treatment in a single visit.…”
Section: Clinical Applicationsmentioning
confidence: 99%